2016
DOI: 10.1139/gen-2015-0192
|View full text |Cite
|
Sign up to set email alerts
|

Can butterflies cope with city life? Butterfly diversity in a young megacity in southern China

Abstract: During 30 years of unprecedented urbanization, plant diversity in Shenzhen, a young megacity in southern China, has increased dramatically. Although strongly associated with plant diversity, butterfly diversity generally declines with urbanization, but this has not been investigated in Shenzhen. Considering the speed of urbanization in Shenzhen and the large number of city parks, we investigated butterfly diversity in Shenzhen parks. We measured butterfly species richness in four microhabitats (groves, hedges,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…The amount of forest edges and clearings, as well as small-scale agricultural mosaics of fields and forests, were found in previous studies to be the most important variables for butterfly diversity (Kivinen, Luoto, Kuussaari, & Saarinen, 2007), possibly due to high oviposition rate and high survival of larvae in those areas (Luoto et al, 2001), in addition to providing nectar resources, efficient sheltered areas to wind and refugees from predators to imagos. At a very local scale, several recent studies have emphasized the role of gardens and urban parks to buffer the negative effect of urbanization on butterflies by providing nectar resources (Fontaine, Bergerot, Le Viol, & Julliard, 2016;Lizee et al, 2016) (Sing, Dong, Wang, & Wilson, 2016). Maintaining sparsely vegetated and semiopen woodlands with glades that constitute important butterfly habitats is a recommended management strategy for conservation goals (Bubova et al, 2015;Nilsson, Franzen, & Pettersson, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of forest edges and clearings, as well as small-scale agricultural mosaics of fields and forests, were found in previous studies to be the most important variables for butterfly diversity (Kivinen, Luoto, Kuussaari, & Saarinen, 2007), possibly due to high oviposition rate and high survival of larvae in those areas (Luoto et al, 2001), in addition to providing nectar resources, efficient sheltered areas to wind and refugees from predators to imagos. At a very local scale, several recent studies have emphasized the role of gardens and urban parks to buffer the negative effect of urbanization on butterflies by providing nectar resources (Fontaine, Bergerot, Le Viol, & Julliard, 2016;Lizee et al, 2016) (Sing, Dong, Wang, & Wilson, 2016). Maintaining sparsely vegetated and semiopen woodlands with glades that constitute important butterfly habitats is a recommended management strategy for conservation goals (Bubova et al, 2015;Nilsson, Franzen, & Pettersson, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Wise land use and floristic planning in green space can serve as refugia for butterflies inside urban areas. Multiple studies have revealed that unmanaged hedges in urban parks; uncommitted weedy patches along river banks, roadsides and medium strips; a diversity of native butterfly attracting plants—both larval host and nectar plants; and landscape heterogeneity are more favorable for butterfly diversity than carefully managed green spaces, alien or monocultural plants, and monotonous landscapes [ 2 , 54 , 159 , 160 , 161 , 162 , 163 , 164 ]. Our 15-year observations in the downtown areas in Kunming also showed similar patterns; butterfly diversity in less managed mosaic habitats is significantly higher than the carefully managed monotonous ones ( Table 3 ).…”
Section: Recommendations Of Future Butterfly Conservationmentioning
confidence: 99%
“…Furthermore, a large number of exotic species have also adapted to this new environment. They have, together, formed a unique urban species pool (Li et al, 2016b;Sing et al, 2016).…”
Section: Effects Of Urban Landscape and Urbanization On Biodiversitymentioning
confidence: 99%